Identification of cell-wall specific protein of mycobacterium tuberculosis by visual comparison of 2-dimensional cytosolic, membrane and cell-wall fractions proteins Gels of m. Tuberculosis. - DIVYA PANDEY,; SUDHIR K. SINHA,; VINEET K. MAURYA, (International Journal of Pharma and Bio Sciences, 2017)
Cell-wall is a very important component of bacteria, which besides making a protective outer covering, saves bacteria from harmful effects of antimicrobials. Mycobacterium tuberculosis (Mtb), causative agent of tuberculosis caused around 10.4 million new infections and 1.8 million deaths worldwide, during 2015. Despite all scientific advancement no new drug or vaccine has released in market for control of TB. Although global incidence rate of TB incidence has shown 1.5% declination (from 2014 to 2015), cases of TB-HIV alliance and single/multiple drug resistance are increasing. Lipid enriched thick cell-wall of Mtb is one of the reason for success of Mtb as human pathogen because it imparts an impervious covering against many drugs. Cell-wall of Mtb can be probed for possible drug targets against tuberculosis, because like other bacteria Mtb cell-wall is of utmost importance to it and any weakening or damage to it would directly affect the survival of bacteria. Concept of visual comparison of classical 1D gel and 2D gels of CW, CM and CST fraction proteins was followed in this study to find out true cell-wall proteins. Comparison of 1DGE gels showed four clear bands, while comparison of 2DGE gels showed six proteins which are supposed to be true cell-wall proteins. This study offers the identification of cell-wall specific proteins with higher probability and saving of time and resources both, compared to methods followed by other.